Physical Activity for Osteoarthritis: A Cross-Sectional Study - Nur Azis Rohmansyah; Sumarjo; Ashira Hiruntrakul (OVS LLC, 2023)
Background. Physical activity is a fundamental and proactive form of conservative treatment for persons with knee osteoarthritis. Study purpose. This study aims to investigate risk variables for individuals in Indonesia who had knee osteoarthritis (OA). Materials and methods. This study's cross-sectional study design employed an observational analytical approach. The samples obtained using Slovin's formula contained as many as 66 respondents. The study's dependent variables were the primary and secondary types of knee OA. Results. The study's dependent variables were the primary and secondary forms of knee OA. 43 patients experienced the primary knee OA, while 23 experienced the secondary OA. The logistic regression test used age (p=0.011), gender (p=0.021), body mass index (p=0.027), history of knee injury (p=0.001), hypertension (p=0.023), hypercholesterolemia (p=0.112), and physical activity (p=0.004) as independent variables. These variables also met the criteria to be incorporated into the multivariate analysis with a p value less than 0.25. The biggest risk factor for knee OA was found to be age (OR=1.923; p=0.011; p=0.011). Knee OA is significantly influenced by age, gender, BMI, a history of knee injuries, and physical activity. Conclusions. Increased physical activity is necessary for those with knee osteoarthritis. Patients with knee osteoarthritis should be treated by healthcare professionals who are aware of their physical activity habits, especially those at risk.